Optimal Multi Zones Search Technique to Detect a Lost Target by Using K Sensors - El-Hadidy, Mohamed; Abou-Gabal, Hamdy; Gabr, Aya (Statistics, Optimization & Information Computing, 2021)
This paper presents the discrete search technique on multi zones to detect a lost target by using sensors. The search region is divided into zones. These zones contain an equal number of states (cells) not necessarily identical. Each zone has a one sensor to detect the target. The target moves over the cells according to a random process. We consider the searching effort as a random variable with a known probability distribution. The detection function with the discounted reward function in a certain state and time interval are given. The optimal effort distribution that minimizes the probability of undetection is obtained after solving a discrete stochastic optimization problem. An algorithm is constructed to obtain the optimal solution as in the numerical application.